The physical activity of Spanish speleologists: accomplishment of recommendations and differences by sociodemographic variables - Miquel Pans; Laura Antón-González; Maite Pellicer-Chenoll (International Journal of Speleology, 2023)
Outdoor adventure activities are becoming more popular due to their potential health benefits, although there is little scientific information on speleology as a physical activity (PA). The purpose of this study is to expand the scientific evidence in this field in two ways: (a) describe the PA performed by speleologists, taking into account the variables of interest such as gender, age, education, speleological level, participation in ‘Alpine’ explorations and body mass index (BMI) and (b) identify how far the World Health Organization’s (WHO) PA recommendations were accomplished (i.e.,150 min of moderate-intensity aerobic PA or 75 min of vigorous-intensity aerobic). A cross-sectional study was conducted on 436 speleologists (305 men, 130 women). The participants completed an electronic survey on PA after which a descriptive analysis and cross-sectional pairwise comparisons (Mann–Whitney U and Kruskal–Wallis tests) were performed on the non-normal data. The mean metabolic equivalent (MET)-minutes/week was 4070.80 (±3078.80) for total PA, 1937.65 (±1992.39) for vigorous PA, 827.66 (±1049.81) for moderate PA and 1304.87 (±1031.65) for PA walking intensity. 73.4% of the participants met the PA recommendations. Nonparametric tests revealed differences by gender, age, educational level and speleological expertise. Women, the middle group age, doctorate and vocational training students, and beginners were less active than their counterparts. The findings provide important contributions towards the positioning and understanding of speleology as a sport and physical activity practice.